'Feels a bit naughty when you're a mum' : alcohol use amongst mothers with preschool children : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology, Massey University, Manawatū, Aotearoa/New Zealand - Pedersen, Michelle (Massey University, 2019)
Over the past two decades, young New Zealand women have consumed alcohol in a culture of normalised intoxication, aligned with postfeminist and neoliberal values of autonomy, fun and freedom of choice. As these women transition into motherhood, they are exposed to contradictory messages on alcohol. Targeted by growing media and advertising messages encouraging alcohol use as a coping strategy for motherhood, they are also expected to conform to ‘good’ mothering ideology. With very little research in this area, the current study aimed to explore the way mothers of preschool children talk about their current alcohol use, their past alcohol use in young adulthood, other mothers’ alcohol use and their partner’s alcohol use. Using a gendered approach the goal was to develop an understanding of how these mothers accepted, resisted and negotiated meanings on alcohol use in early motherhood and how their drinking was negotiated with their partners and parental responsibilities. Following ethical approval, seven friendship discussion groups, involving 30 mothers between ages 28 and 41 were conducted in Wellington, New Zealand. Transcribed discussions were subject to Foucauldian discourse analysis, which showed that the women drew upon the ‘work hard, play hard’ and ‘developmental age and stage’ discourses to normalise excessive drinking and experimentation in young adulthood. In comparison, current drinking was discussed as routine and constructed as a ‘reward’, for ‘relaxation’ and as a form of ‘adult time out’, providing these mothers with a way to cope and a brief escape from the demands of mothering. Unlike fathers’ drinking, which was constructed as ‘masculine’, the mothers’ drinking was highly policed and sanctioned through public ‘surveillance’ and their own ‘self-monitoring’. Mothers who deviated from idealised expectations of ‘good’ mothering were seen as lower-class. Although a ‘considerate family man’ discourse was drawn upon, it was the mothers who still took on the primary caregiving role. They often instigated couple negotiations on who was drinking and it was frequently their drinking (rather than fathers) that was restricted due to parental responsibilities. Findings are discussed in terms of what this means for public health campaigns, women’s access to alcohol support as well as wider implications for gender relations.
Keywords: Mothers; Attitudes; Alcohol use; Drinking of alcoholic beverages; New Zealand; 520304 Health psychology